Cultural Representations and Verbal and Visual LGBT Repertoires in Market Segmentation and Advertising of Todes Telecom (Revista Internacional de Folkcomunicação, 2025)
Since the 1990s, market offers aimed at the LGBTQIAPN+ public have expanded, accompanied by advertising practices that incorporate symbolic repertoires representative of this segment. This exploratory and qualitative study aims to analyze how the telephone company Todes Telecom uses these representations in developing messages and offers aimed at the gender-diverse audience. The research is based on an analysis of advertising materials, complemented by a literature review guided by Cultural Studies (Hall, 2006; 2016; 2018). The results demonstrate that the brand's advertising mobilizes cultural elements of the LGBTQIAPN+ spectrum, articulating verbal and visual repertoires in formulating messages capable of fostering notable communication with this audience.